Heads up! early warning systems for climate-, water- and weather-related hazards - Glantz, Michael H. (United Nations University Press, 2009)
This publication provides a review of early warning systems in operation, while exploring a range of hazards including hurricanes, heat waves, floods, droughts, tsunami and volcanoes.--Publisher's description.